The International Journal of Acoustics and Vibration 2020
DOI: 10.20855/ijav.2020.25.41702
|View full text |Cite
|
Sign up to set email alerts
|

Active and Passive Suspension System Performance under Random Road Profile Excitations

Abstract: Passive suspensions are designed to satisfy the conflicting criteria of riding comfort and vehicle handling. An active suspension system attempts to overcome these compromises to provide the best performance for vehicle control. Different types of mathematical models have been used to study the suspension system of a vehicle. The quarter vehicle model is used for initial investigation. Later, the half vehicle and full vehicle models are used for the study, which is closer to the actual model of a vehicle suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The dispersion models namely, the standard deviation and mean were employed to evaluate the data accuracy either convergent or divergent type and also to find out the stability of the data. A small value for the standard deviation was indicated that the value tended to be close to the mean [24]. In this study, the standard deviation produced by the experimental work was 0.01 while the standard deviation from the mathematical modelling was 0.005.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The dispersion models namely, the standard deviation and mean were employed to evaluate the data accuracy either convergent or divergent type and also to find out the stability of the data. A small value for the standard deviation was indicated that the value tended to be close to the mean [24]. In this study, the standard deviation produced by the experimental work was 0.01 while the standard deviation from the mathematical modelling was 0.005.…”
Section: Discussionmentioning
confidence: 48%
“…Different suspension systems were fulfilled the constraint of an energy efficiency using various approaches [23]. The quarter vehicle model was used as an initial investigation, in which the model was closely resembled the actual model of the car [24]. Ride safety and the handling capabilities of the vehicle are mainly determined by the suspension system which transmit the forces between the vehicle and the road.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The suspension system works as the essential interface between the vehicle and the road. 8,9 The design of an automobile vehicle suspension has been the subject of research for a long time. Generally speaking, a decent suspension must provide a comfortable ride and good vehicle handling within a reasonable range of suspension deflection.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the design of spring suspension not only for tractor, but also for automobile trailers, both domestic and foreign, it can be seen that the overwhelming majority of them consist of leaf springs [6]. Despite their simplicity of design and efficiency of use, they have significant disadvantages such as -high metal consumption and rigidity, high labor intensity during repair work, relatively high cost [7]. At the same time, in the practice of this direction in mechanical engineering, not only leaf springs are used as spring suspension, but also helical compression springs, pneumatic and torsion springs.…”
Section: Introductionmentioning
confidence: 99%